Creative training a user's guide. (Voluntary Service Overseas, 1998)
A compilation of useful strategies and approaches for workshop training. Intended for use by those conducting seminars in different media or special courses. The material itself is presented in an easy to read format using simple terms and several illustrations enabling most readers to apply the discussed techniques for their own use.